From the Traditional to the Modern: The Culture of Kindergartens Communities That Learn (The Croatian Experience) - Ljubetić, Maja (Array, 2012)
Even though the tradition of kindergartens in Croatia is a long one, it is only since the last decade that kindergartens in the Republic of Croatia have been regarded as communities that learn. For many years, the function of traditional kindergartens was determined by the philosophy and the beliefs of a totalitarian socialistic social order which, with the transition to democracy, accepted new paradigms about a child's development, learning, institutional upbringing and the education of pre-school aged children etc. New democratic values have become an integral part of early childhood and pre-school education institutions and have also initiated changes in educational programmes for kindergarten-school teachers. An important segment in this “new vision” of institutions for early childhood and pre-school education is the culture of the institution. All participants in the upbringing- educational process play an active role in the development of this culture. The quality of the community's culture determines the quality of life and learning of both adults and children in that community. Therefore, it is necessary to dedicate greater attention to raising awareness of and improving culture.